The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijms221910517
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Lipoproteins and Cholesterol Alterations after Sepsis: Implication for Atherosclerosis Progression

Abstract: (1) Background: Sepsis is one of the most common critical care illnesses with increasing survivorship. The quality of life in sepsis survivors is adversely affected by several co-morbidities, including increased incidence of dementia, stroke, cardiac disease and at least temporary deterioration in cognitive dysfunction. One of the potential explanations for their progression is the persistence of lipid profile abnormalities induced during acute sepsis into recovery, resulting in acceleration of atherosclerosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 200 publications
1
8
0
Order By: Relevance
“…Univariate and multivariate analyses demonstrated that HDL-c was an independent prognostic factor for survival. These results are consistent with prior findings that the level of cholesterol and lipoproteins is one of the hallmarks of survival and demise in critical illness and inflammatory disorders ( 6 , 24 26 ). Tanaka et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Univariate and multivariate analyses demonstrated that HDL-c was an independent prognostic factor for survival. These results are consistent with prior findings that the level of cholesterol and lipoproteins is one of the hallmarks of survival and demise in critical illness and inflammatory disorders ( 6 , 24 26 ). Tanaka et al.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have suggested that serum lipid levels can indirectly measure pro-inflammatory cytokine bioactivity, even without obesity, diabetes, and metabolic syndrome ( 5 ). Additionally, components of cholesterol metabolism are essential in response to infection by moderating the immunological response during acute septic episodes ( 6 ). Moreover, the serum cholesterol levels may reflect a metabolic response of the organism to the inflammatory condition in septic patients, independent of diet or treatment ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is also the precursor of all steroid hormones and bile acids and plays a key role in membrane trafficking, transmembrane signaling processes, and cell proliferation [ 42 , 43 , 44 , 45 , 46 ]. Cholesterol is typically transported as lipoproteins, which consist of TG and cholesterol in the center surrounded by a phospholipid shell with apolipoprotein embedded in them [ 47 , 48 ]. The relationship between lipids and cognition is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have investigated serum levels of lipoproteins and lipid classes in patients with sepsis; these results have been discussed in several recent reviews [ 98 , 99 , 100 , 101 , 102 ]. First, sepsis patients show decreased levels of High (HDL) and Low density (LDL) lipoproteins, and these levels are inversely correlated with the levels of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%